Mechano-regulation of stem cell differentiation and tissue regeneration in osteochondral defects - KELLY, DANIEL; Prendergast, Patrick John (Elsevier, 2005)
Cartilage defects that penetrate the subchondral bone can undergo spontaneous repair through the formation of a fibrous or cartilaginous tissue mediated primarily by mesenchymal stem cells from the bone marrow. This tissue is biomechanically inferior to normal articular cartilage, and is often observed to degrade over time. The factors that control the type and quality of the repair tissue, and its subsequent degradation, have yet to be elucidated. In this paper, we hypothesise a relationship between the mechanical environment of mesenchymal stem cells and their subsequent dispersal, proliferation, differentiation and death. The mechano-regulation stimulus is hypothesised to be a function of strain and fluid flow; these quantities are calculated using a finite element model of the tissue. A finite element model of an osteochondral defect in the knee was created, and used to simulate the spontaneous repair process. The model predicts bone formation through both endochondral and direct intramembranous ossification in the base of the defect, cartilage formation in the centre of the defect and fibrous tissue formation superficially. Greater amounts of fibrous tissue formation are predicted as the size of the defect is increased. Large strains are predicted within the fibrous tissue at the articular surface, resulting in significant cell apoptosis. This result leads to the conclusion that repair tissue degradation is initiated in the fibrous tissue that forms at the articular surface. The success of the mechano-regulation model in predicting many of the cellular events that occur during osteochondral defect healing suggest that in the future it could be used as a tool for optimizing scaffolds for tissue engineering.
PUBLISHED
Keywords: Mechanical & Manufacturing Engineering